Bilateral Deep Brain Stimulation is the Procedure to Beat for Advanced Parkinson Disease: A Meta-Analytic, Cost-Effective Threshold Analysis for Focused Ultrasound. Issue 3 (9th March 2021) - Mahajan, Uma V; Ravikumar, Vinod K; Kumar, Kevin K; Ku, Seul; Ojukwu, Disep I; Kilbane, Camilla; Ghanouni, Pejman; Rosenow, Joshua M; Stein, Sherman C; Halpern, Casey H
Abstract: BACKGROUND: Parkinson disease (PD) impairs daily functioning for an increasing number of patients and has a growing national economic burden. Deep brain stimulation (DBS) may be the most broadly accepted procedural intervention for PD, but cost-effectiveness has not been established. Moreover, magnetic resonance image-guided focused ultrasound (FUS) is an emerging incisionless, ablative treatment that could potentially be safer and even more cost-effective. OBJECTIVE: To (1) quantify the utility (functional disability metric) imparted by DBS and radiofrequency ablation (RF), (2) compare cost-effectiveness of DBS and RF, and (3) establish a preliminary success threshold at which FUS would be cost-effective compared to these procedures. METHODS: We performed a meta-analysis of articles (1998-2018) of DBS and RF targeting the globus pallidus or subthalamic nucleus in PD patients and calculated utility using pooled Unified Parkinson Disease Rating Scale motor (UPDRS-3) scores and adverse events incidences. We calculated Medicare reimbursements for each treatment as a proxy for societal cost. RESULTS: Over a 22-mo mean follow-up period, bilateral DBS imparted the most utility (0.423 quality-adjusted life-years added) compared to (in order of best to worst) bilateral RF, unilateral DBS, and unilateral RF, and was the most cost-effective (expected cost: $32 095 ± $594) over a 22-mo mean follow-up. Based on this benchmark, FUS would need to impart UPDRS-3 reductions of ∼16% and ∼33% to be the most cost-effective treatment over 2- and 5-yr periods, respectively. CONCLUSION: Bilateral DBS imparts the most utility and cost-effectiveness for PD. If our established success threshold is met, FUS ablation could dominate bilateral DBS's cost-effectiveness from a societal cost perspective. Graphical Abstract: